2011
DOI: 10.1002/ab.20416
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Depression and Anxiety to Self‐ and Peer‐Reported Relational Aggression

Abstract: The primary purpose of this multimethod and multimeasure study was to identify how the peer relationships of Australian adolescents (ages 9-15 years; N = 335) at school, including relational aggression and victimization, correlated with their symptoms of depression and anxiety. Moreover, relational aggression and victimization were measured via both self- and peer report, and discrepancies between reports were considered as correlates of symptoms and peer relationship status. Adolescents who reported more symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 83 publications
0
18
1
5
Order By: Relevance
“…Another limitation is the use of self-report only. Although it is important to consider perceptions and personal reports, research has demonstrated that there may be differences between correlates of perceptions and correlates of similar constructs based on other informants (Hoffman, Cole, Martin, Tram, & Seroczynski, 2000;Zimmer-Gembeck & Pronk, 2012). However, standardized stimuli were provided to assess the adolescents' anticipated responses to rejection to improve validity and accuracy over retrospective recall (by self or peers) of actual events and reactions.…”
Section: Discussionmentioning
confidence: 98%
“…Another limitation is the use of self-report only. Although it is important to consider perceptions and personal reports, research has demonstrated that there may be differences between correlates of perceptions and correlates of similar constructs based on other informants (Hoffman, Cole, Martin, Tram, & Seroczynski, 2000;Zimmer-Gembeck & Pronk, 2012). However, standardized stimuli were provided to assess the adolescents' anticipated responses to rejection to improve validity and accuracy over retrospective recall (by self or peers) of actual events and reactions.…”
Section: Discussionmentioning
confidence: 98%
“…Response options for each item ranged from 1 (not at all true) to 5 (very true). Items were developed by Crick and Grotpeter (1995) and extended by Zimmer-Gembeck and Pronk (2012). An example overt aggression item was, "I threaten to or do push, shove or hit other kids."…”
Section: Methodsmentioning
confidence: 99%
“…Second, all data were collected via self-report, which may have inflated some of the associations reported here. Although it is important to consider perceptions and personal reports of behavior when studying RS, blame and behavioral responses to rejection threat, research has demonstrated that there may be differences between correlates of perceptions and correlates of similar constructs based on other informants (Hoffman et al 2000;Nuijens et al 2009;ZimmerGembeck et al 2007;Zimmer-Gembeck and Pronk 2012). However, standardized stimuli were provided to assess the adolescents' anticipated responses to rejection threat to improve validity and accuracy over retrospective recall (by self or peers) of actual events and reactions.…”
Section: Implications and Recommendations For Future Researchmentioning
confidence: 98%
“…There is much research that shows the detrimental impact of peer rejection on children's mood, affect and depressive symptoms, as well as their negative attitudes towards their peers (Bagwell, Schmidt, Newcomb, & Bukowski, 2001;Borelli & Prinstein, 2006;Murray-Close, Ostrov, & Crick, 2007;Zimmer-Gembeck & Pronk, 2012). Research has also demonstrated that RS uniquely contributes to negative mood (Downey & Feldman, 1996;Downey et al, 1998) and depressive symptoms (Ayduk et al, 2001;Romero-Canyas & Downey, 2005), even after accounting for actual experiences of peer rejection.…”
Section: Attitudes Towards the In-group And Negative Moodmentioning
confidence: 99%